Denying the Dichotomy: Word Images in The Waves - Bernadette McCarthy (Cahiers Victoriens et Edouardiens)
Roger Fry’s introduction to Britain of the works of Post-impressionist painters was to impact significantly on the artistic development of writers including Virginia Woolf. Out of this convergence of visual and verbal thought, The Waves emerged; a literary work deeply implicated in visual convention. Its pictorial interludes represent an inseparable union of word and image. I propose to examine these passages with a visual art critical lens and to consider them as one would a series of paintings.